Exploring the benchmarks of the Taiwanese investment trust corporations: Management and investment efficiency perspectives - Lu W.-M.; Liu J.S.; Kweh Q.L.; Wang C.-W. (Elsevier, 2023)
Data envelopment analysis; Economics; Efficiency; Efficiency decomposition; Investment efficiency; Investment strategy; Management efficiency; Mutual fund managers; Network-based; Operating performance; Performance; Investments